The role of phages for microdiverse bacterial communities in proglacial stream biofilms - Peter, Hannes; Michoud, Grégoire; Busi, Susheel Bhanu; Battin, Tom J. (Frontiers in Microbiomes, 2024)
Viruses modulate the diversity and activity of microbial communities. However, little is known about their role for the structure of stream bacterial biofilm communities. Here, we present insights into the diversity and composition of viral communities in various streams draining three proglacial floodplains in Switzerland. Proglacial streams are characterized by extreme environmental conditions, including near-freezing temperatures and ultra-oligotrophy. These conditions select for few but well-adapted bacterial clades, which dominate biofilm communities and occupy niches via microdiversification. We used metagenomic sequencing to reveal a diverse biofilm viral assemblage in these streams. Across the different floodplains and streams, viral community composition was tightly coupled to that of the bacterial hosts, which was underscored by generally high host specificity. Combining predictions of phagehost interactions with auxiliary metabolic genes (AMGs), we identify specific AMGs shared by phages infecting microdiverse clade members. Our work provides a step towards a better understanding of the complex interactions among bacteria and phages in stream biofilm communities in general and streams influenced by glacier meltwaters and characterized by microdiversity in particular.